2017
DOI: 10.11158/saa.22.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A life table analysis to evaluate biological control of banks grass mite using the predatory mite, Galendromus flumenis (Acari: Phytoseiidae)

Abstract: A life table analysis to evaluate biological control of banks grass mite using the predatory mite, Galendromus flumenis (Acari: Phytoseiidae) FATEMEH AbstractThe predatory mite, Galendromus flumenis (Chant) (Acari: Phytoseiidae), has shown promising traits for biological control of Banks grass mite, the major pest of date palms in California. In the present study, reproduction and population growth parameters of G. flumenis on Banks grass mite eggs were studied at 34ºC, 50±10% RH and a photoperiod of 16: 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For PHM in dates, it is essential to consider the effects of candidate chemicals on the two important parasitoids of the pink hibiscus mealybug in the Coachella Valley, A. callidus and G. indica . In addition, it is important to consider the impact on Galendromus flumenis (Chant), which is a key predator for another major pest of dates, the Banks grass mite, Oligonychus pratensis (Banks) [49,50]. Several studies have shown that bifenthrin and fenpropathrin are extremely toxic to beneficial arthropods, including the parasitoid wasps and the predatory mites [48,51,52,53,54,55]; therefore, the use of these pyrethroids should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…For PHM in dates, it is essential to consider the effects of candidate chemicals on the two important parasitoids of the pink hibiscus mealybug in the Coachella Valley, A. callidus and G. indica . In addition, it is important to consider the impact on Galendromus flumenis (Chant), which is a key predator for another major pest of dates, the Banks grass mite, Oligonychus pratensis (Banks) [49,50]. Several studies have shown that bifenthrin and fenpropathrin are extremely toxic to beneficial arthropods, including the parasitoid wasps and the predatory mites [48,51,52,53,54,55]; therefore, the use of these pyrethroids should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Galendromus occidentalis fed with mobile stages of T. pacificus got a rm = 0.20 females female -1 d -1 (Bruce-Oliver and Hoy, 1990). Ganjisaffar and Perring (2017) recorded a similar rm value for Galendromus flumenis (Acari: Phytoseiidae) reared with eggs of Oligonychus pratensis (Banks) (Acari: Tetranychidae). Our results yielded a rm = 0.19 females female -1 d -1 , when they preyed on all stages of O. yothersi.…”
Section: Life Table Parameters Of Galendromus Occidentalis Preying On...mentioning
confidence: 94%